The Palermo Convention/1. The intergovernmental cooperation of the 1990s (Rivista di Studi e Ricerche sulla criminalità organizzata, 2019)
The purpose of this paper is to track the progress of the negotiations that led in 2000 to the adoption of the UN Convention against Transnational Organized Crime and its three supplementary protocols. Starting with the UN Congresses on the Prevention of Crime and the Treatment of Offenders this study especially focuses on two turning points of this long-term process, namely the establishment of a Commission on Crime Prevention and Criminal Justice in 1991, and the World Ministerial Conference held in Naples in November 1994, which adopted the Naples Political Declaration and a Global Action Plan against Organized Transnational Crime.Key words: UN Convention against Transnational Organized Crime; Commission on Crime Prevention and Criminal Justice; UN Congresses on the Prevention of Crime and the Treatment of Offenders.